1975
DOI: 10.1136/vr.97.19.366
|View full text |Cite
|
Sign up to set email alerts
|

Plasma oestrogen and progesterone in relation to superovulation and egg recovery in the cow

Abstract: Pregnant mares serum gonadotrophin (PMSG) was used in combination with prostaglandin F2alpha or its analogues to induce superovulation in 25 heifers. Total unconjugated oestrogen and progesterone were determined in peripheral plasma of these superovulated animals, and the levels compared with those found during the normal oestrous cycle. A very high level of oestrogen was found between day 3 and 6 after superovulation, and it seems likely that large unovulated follicles were responsible for the excess steroid.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
18
1

Year Published

1977
1977
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 0 publications
6
18
1
Order By: Relevance
“…The oocytes from such ovaries are used in many studies on maturation despite reports showing lowered fertilization rates and increased preimplantation losses associated with these procedures (Miller & Armstrong, 1981;Evans & Armstrong, 1983). The cause of the embryonic abnormalities has previously been ascribed to the elevated levels of circulating steroid in PMSG-treated animals (Booth, Newcomb, Strange, Rowson & Sacher, 1975). Our results confirm that PMSG causes excessive follicular steroid secretion but also focusses attention on the adverse effects of this gonadotrophin on the maturing oocyte.…”
Section: Methodssupporting
confidence: 78%
“…The oocytes from such ovaries are used in many studies on maturation despite reports showing lowered fertilization rates and increased preimplantation losses associated with these procedures (Miller & Armstrong, 1981;Evans & Armstrong, 1983). The cause of the embryonic abnormalities has previously been ascribed to the elevated levels of circulating steroid in PMSG-treated animals (Booth, Newcomb, Strange, Rowson & Sacher, 1975). Our results confirm that PMSG causes excessive follicular steroid secretion but also focusses attention on the adverse effects of this gonadotrophin on the maturing oocyte.…”
Section: Methodssupporting
confidence: 78%
“…Similar results have been reported in ewes [10] and goats [11]. However, prematurely regressed CL has been observed in suprovulated ewes [12][13][14], cows [15] and goats [16][17][18]. Ryan et al [13] reported that the proportion of ewes that ovulated and subsequently had M chorionic gonadotropin (eCG) has been conventionally used for superovulation in ewes [1][2][3][4].…”
supporting
confidence: 64%
“…Similar findings were obtained in previous studies in which cows were superovulated with various doses of PMSG [7][8][9],HMG [10] and FSH-P [11]. These studies suggested that the ovarian response and variability in ova/embryo quality increased with the dose.…”
Section: Discussionsupporting
confidence: 79%